2022
DOI: 10.1177/02692155221133474
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of robotic-assisted gait training on cardiopulmonary fitness and exercise capacity for incomplete spinal cord injury: A systematic review and meta-analysis of randomized controlled trials

Abstract: Objective To determine the effects of robotic-assisted gait training on cardiopulmonary fitness and exercise capacity for people with incomplete spinal cord injury. Methods PubMed, Embase, Web of Science, PEDro, CENTRAL and CINAHL were searched from inception until September 4, 2022. Randomized controlled trials that evaluated the effects of robotic-assisted gait training on cardiopulmonary fitness and exercise capacity for individuals with incomplete spinal cord injury were selected. Mean differences (MD) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…We observed clinical improvement in both the control and experimental study groups; however, there were greater effects (in functional gait parameters) in the RAGT group. These results are consistent with reports from the literature [14][15][16]34,36]. In a study by Labruyère et al, no such relationship was observed [37]; however, the study included a small group of only nine patients with incomplete SCI (AIS-C and D).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed clinical improvement in both the control and experimental study groups; however, there were greater effects (in functional gait parameters) in the RAGT group. These results are consistent with reports from the literature [14][15][16]34,36]. In a study by Labruyère et al, no such relationship was observed [37]; however, the study included a small group of only nine patients with incomplete SCI (AIS-C and D).…”
Section: Discussionsupporting
confidence: 92%
“…Regular locomotor training can also prevent secondary problems associated with physical inactivity in SCI patients. RAGT has been shown to have beneficial effects in reducing pain, spasticity, or improving cardiopulmonary, urinary, and bowel functions [4,11,[14][15][16]. The greatest effects of RAGT are observed in Diagnostics 2023, 13,1966 2 of 15 individuals with incomplete SCI and in the early stages of this therapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…It ultimately shortens patients’ life expectancy 5. In addition, the mortality rate of patients with SCI is higher than that of the general population 6–8. National statistical data show an increasing incidence rate of SCI annually, and that the incidence rate of SCI per million residents is 9.3 persons/year 9.…”
Section: Introductionmentioning
confidence: 99%
“… 13 RAGT can also improve balance function and has been gradually applied in patients with SCI. 14 In patients with SCI, robots for lower limb rehabilitation can effectively and safely improve walking ability; reduce pressure ulcers, 15 lung infections, 8 urinary tract infections and other complications 16 ; improve dignity; and reduce costs. However, high-quality evidence-based medical studies that systematically evaluated the efficacy of RAGT in the treatment of SCI remain scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation